HUBUNGAN BEBERAPA FAKTOR PADA WANITA PUS DENGAN KEIKUTSERTAAN KB SUNTIK DI DESA DUREN KECAMATAN SUMOWONO KABUPATEN SEMARANG - Ryan Adiputra; Djoko Nugroho; Sri Winarni; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2016)
In Duren Vilage, Sumowono District, Semarang amongst the woman who uses contraceptive the percentage of injectable contraceptive user is only 26%, the lowest compared to other village. The goal of this research is to analyze the correlation between the factors affecting the participations of injectable contraceptive usage. This is an Explanatory Research which uses Cross Sectional Study method. The population of fertile married woman is 109 person where 80 people are selected as samples using the purposive sampling method. 21 percent of the samples are injectable contraceptive participants. Data will be analyzed  using univariat and bivariat method. The bivariat method uses chi square. This resaerch shows that there are no correlation between the predisposing factors {(parity (p=0,599), age (p=0,169), fertile woman attitude (p=0,052), family income (p=1,000)}, enabling factors {(the availability of injectible contraceptive (p=0,86)} and the reinforcing factors {(husband support (p=0,521), neighbour support (p=0,725), dan PLKB support (p=1,000)} with the participation of injectible contraceptive. There is a correlation the availability of information related to contraception (p=0,014) (enabling factor) with the the participations of injectable contraceptive. In conclusion, there are 1 factors which is related to the participations of injectable contraceptive amogst fertile married woman. It is adviced that the obstetrician work together with the volunteers to futher communicate the information related to injectable contraceptive.